Morphological ontogeny of Liebstadia mongolica (Acari: Oribatida: Scheloribatidae), with comments on Liebstadia Oudemans - Seniczak, Stanisław; Seniczak, Anna; Kaczmarek, Sławomir; Marquardt, Tomasz; Sarsenova, Bibigul (Zootaxa, 2020)
The morphological ontogeny of Liebstadia mongolica Bayartogtokh, 2001 is described and illustrated. The juveniles of this species are elongated and unpigmented. The larva has 12 pairs of gastronotal setae, and three of them are with excentrosclerites (c2, la, lp), the nymphs have 15 pairs, and five of them are with excentrosclerites (c2, la, lp, h2, h3). In all instars, solenidion ω1 on tarsus I is curved laterally, and is shorter than ω2.